214 REGULATION OF CELLULAR CREATINE HOMEOSTASIS: A ROLE FOR THIOREDOXIN INTERACTING PROTEIN (TXNIP). (24th May 2013) - Zervou, S; Ray, T; Cross, R; Sahgal, N; Sebag-Montefiore, L; Medway, D; Ostrowski, P; Neubauer, S; Lygate, C
Abstract : Background: Creatine (Cr) uptake across the plasma membrane is particularly important in excitable cells that cannot synthesise Cr, such as cardiomyocytes, where creatine has a role in energy buffering and transport. Uptake is tightly controlled via a specific transmembrane Creatine Transporter (CrT), while cellular loss is slow, passive, and non-enzymatic. Earlier work has suggested that CrT activity is subject to substrate inhibition, but, that this requires de novo synthesis of unidentified protein(s). The purpose of this study was to identify this protein and to verify its role as a potential endogenous inhibitor of the CrT. Methods and Results: To achieve this we took a global gene array approach under varying conditions of cellular [Cr], and verified our findings using an in vitro assay of Cr-uptake using a radiolabelled 14 Cr method. 3T3 fibroblasts stably over-expressing CrT were incubated for 2-5 hours with either low (250 µM) or saturating (5 mM) Cr, with and without cycloheximide (CHX) to inhibit protein synthesis. Cr uptake plateaued at 3 hours in response to saturating levels of extracellular Cr (5mM) and was 33% ( P <0.01) higher in the presence of CHX, suggesting synthesis of a protein involved in regulating further Cr uptake. Global gene expression analysis using the Illumina Mouse WG6v2 Expression BeadChip system identified thioredoxin interactingprotein (Txnip) as the only significantly up-regulated gene under these conditions, elevated by 40% compared to non-treated cells ( P =0.036). Quantitative RT-PCR verified up-regulation of Txnip mRNA (61% increase; P=0.002 ) and immunoblotting detected a 45% increase in Txnip protein after 3hr of Cr incubation ( P=0.01 ). Treatment of cells with either 250 µM Cr or 5mM taurine, did not result in Txnip mRNA or protein up-regulation, confirming specificity for saturating Cr. Small interfering RNA against Txnip (siTxnip) reduced mRNA levels by 50% and attenuated the increase in Txnip gene expression in response to 5mM Cr (17% in siTxnip versus 45% in control cells). This was sufficient to maintain CrT activity at control levels during high [Cr], i.e. substrate inhibition was completely abolished. The in vitro observations were tested in vivo in relation to altered left ventricular [Cr]. Cr-deficient mice, due to deletion of the Cr biosynthetic enzyme guanidinoacetate methyl-transferase (GAMT −/− ), had LV Txnip mRNA 35% lower than wild-types. Conversely, mice with cardiac overexpression of CrT had elevated LV [Cr] (mean 124 versus 74nmol/mg protein in WT) associated with a 58% increase in Txnip mRNA and 29% more Txnip protein when compared to wild-type littermates. Conclusion: Our work suggests a novel role for Txnip in the endogenous regulation of CrT activity in cardiomyocytes, thereby contributing to modulation of Cr homeostasis. The molecular mechanisms involved in the CrT-Txnip interaction, merit further elucidation.